Spain : Financial Sector Assessment Program-Technical Note-Impaired Assets and Nonperforming Loans. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain in the areas of impaired assets and nonperforming loans (NPLs). The size of the problem assets varies significantly across banks and is concentrated in those exposed to residential mortgages and real-estate-related firms, whose NPLs represent about 57 percent of all NPLs. A tough stance on the implementation of the European Central Bank (ECB) guidance on NPLs is desirable. Ideally, in the case of Spain, the cleanup should be completed before the expiration of the ECB's long-term support. Targets to reduce problem assets should be ambitious, and failure to comply should have prudential consequences.